Impact of repetitive transcranial magnetic stimulation on clinical and cognitive outcomes, and brain-derived neurotrophic factor levels in treatment-resistant depression - Ginelli, Enrico; Sanna, Lucia; Paribello, Pasquale; Isayeva, Ulker; Corona, Giorgio; Zai, Clement C.; Manca, Daniela; Iaselli, Maria Novella; Collu, Roberto; Pinna, Federica; Scherma, Maria; Manchia, Mirko; et al. (Frontiers in Psychiatry, 2025)
IntroductionTreatment-resistant depression (TRD) affects approximately 30% of patients with major depressive disorder (MDD), for whom effective treatment options are limited. Repetitive transcranial magnetic stimulation (rTMS) has shown efficacy in alleviating depressive symptoms in TRD. However, it remains unclear if these improvements are driven or mediated by changes in cognitive function or biological markers, such as brain-derived neurotrophic factor (BDNF).MethodsThis study examines the effects of rTMS on depressive symptoms, cognition, and BDNF levels, as well as the potential moderating role of lifetime suicidal attempts (LSA) on cognition and the predictive value of baseline BDNF for clinical outcomes. Twenty-five TRD patients were included, with 13 in the rTMS treatment group (receiving 20 sessions of rTMS over four weeks) and 12 as control group. Depression severity, cognitive function (Mini-Mental State Examination, Verbal Fluency, Digit Span), and serum BDNF levels were measured pre- and post-treatment. Mixed-effects linear regression models assessed clinical and biological associations.ResultsrTMS significantly reduced HAM-D (p < 0.001) and CGI (p < 0.001) scores compared to controls. Cognitive performance improved significantly in MMSE (p = 0.049) and Digit Span (p = 0.04), with no significant changes in BDNF levels (p = 0.39). LSA did not moderate cognitive outcomes, and baseline BDNF did not predict clinical improvement (p = 0.68).DiscussionrTMS reduced depressive symptoms in TRD patients, with modest cognitive benefits. Baseline BDNF did not predict outcomes, though the lack of significant change suggests complex neuroplastic responses. Future studies should include larger samples and refined biomarker assessments.